Computer-Aided Instruction for Large Elementary Courses - Booms, Bernard H.; Kaltreider, D. Lynne (American Economic Review, 2016)
Large classes are an important element of higher education in the United States today. Pressures of increased enrollment and shrinking financial support are likely to insure the continued existence of large classes in our colleges and universities, even though a sizable proportion of both students and faculty view this technique of instruction as unsatisfactory. With increased size have come changes in the organization, atmosphere, activity, and acceptability of the classroom scene. In the typical large enrollment course, the professor meets the students en masse several times a week for lectures and demonstrations, and once a week the students are expected to attend small recitations